2004
DOI: 10.1002/pc.20031
|View full text |Cite
|
Sign up to set email alerts
|

Non‐isothermal flow of a polymeric liquid through rounded rectangular ducts

Abstract: The 3D non-isothermal creeping flow of nylon-6 in a bent rectangular duct is studied numerically. A differential-type non-isothermal White-Metzner constitutive equation is used for this flow simulation. Computational results are obtained by the elastic-viscous split-stress (EVSS) finite element method, incorporating the streamline-upwind Petrov-Galerkin (SUPG) scheme. The generated thermal field is entirely due to viscous heating. Essential flow characteristics, including temperature distribution in the flow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Several theoretical and computational investigations were carried out to analyze the effect of secondary flows on the flow field for 3D geometries using different constitutive models such as Criminale‐Ericksen‐Filbey (CEF), Reiner‐Rivlin, Oldroyd‐3‐constant model, White‐Metzner model, Phan‐Thien‐Tanner (PTT) model, and Giesekus model . It was reported that the magnitude of these secondary vortices in the transversal cross‐section is usually lower than the longitudinal flow.…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical and computational investigations were carried out to analyze the effect of secondary flows on the flow field for 3D geometries using different constitutive models such as Criminale‐Ericksen‐Filbey (CEF), Reiner‐Rivlin, Oldroyd‐3‐constant model, White‐Metzner model, Phan‐Thien‐Tanner (PTT) model, and Giesekus model . It was reported that the magnitude of these secondary vortices in the transversal cross‐section is usually lower than the longitudinal flow.…”
Section: Introductionmentioning
confidence: 99%